Exploring Factors and Associate Responses for Anxiety in the Coronavirus Disease 2019 Pandemic: A Web-Based Survey in Japan - Zhuang, Jinman; Cai, Guoxi; Lu, Yixiao; Xu, Xinying; Lin, Yulan; Wong, Li Ping; Hu, Zhijian; Yamamoto, Taro; Morita, Kouichi; Aoyagi, Kiyoshi; He, Fei (Frontiers in Psychology, 2022)
Background and objectives: Anxiety plays an important role in psychology. An exploration of anxiety and its associated reactions may provide insight into measures for addressing mental health problems caused by the COVID-19 pandemic. Data from this study provides potential correlational responses to anxiety.Methods: A cross-sectional study using data collected via an online self-reported questionnaire was conducted in Japan during the COVID-19 pandemic. Using the State-Trait Anxiety Inventory (STAI-6), to we assessed anxiety levels and explored the relationship between anxiety STAI-6 Score, sources of COVID-19 information, the influences of COVID-19, social anxiety symptoms, discrimination, and evaluation of the government.Results: A total of 4,127 participants were included to in the analysis. The level of anxiety was not equally distributed across the general population with respect to age, gender, educational level, occupation, income, presence of underlying disease, and location (P < 0.05). The number of sources of information on COVID-19 had a positive correlation with the STAI-6 Score (Spearman’s rho = 0.176, P < 0.001). The influence of the pandemic was correlated with moderate–severe anxiety. A high level of anxiety added to social anxiety (Spearman’s rho = 0.04, P < 0.05) and discriminatory behavior (Spearman’s rho = 0.11, P < 0.01). Being female (Estimate=0.926) and from a non-emergency area (Estimate=-0.308) was related to higher STAI scores, and higher education (Estimate=-0.305) and income (Estimate=-0.168) decreased the STAI score. The respondents who had a lower evaluative score of the preventive activities undertaken by the national and local governments had higher STAI-6 Scores. Conclusions: Our findings provide statistical evidence for the associated reaction of anxiety and that anxiety reactions may vary in predictable ways. Further studies should focus on strategic interventions that may decrease associated responses to anxiety, to address mental health issues due to the pandemic.